Parent’s Efforts on Shaping the Self-Reliance of Students Drop Out of School - Sisrika Hayatul Rahmi; Wisroni Wisroni (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
This research was motivated by the high independence of school dropouts in Jorong Koto Baru Lembah Gumanti District, Solok Regency, which was marked by their own income and their participation in community activities. The independence of teenagers dropping out of school was allegedly due to the efforts of parents in establishing their independence. The total population in this study were 25 teenagers who dropped out of school with a sampling of 60% so that there were 15 people. Data analysis techniques used are quantitative descriptive with percentage calculation. The results of the study found that, (1) the opportunity given by parents, (2) communication conducted by parents, and (3) the responsibility given in the formation of independence in Jorong Koto Baru was categorized as very good.Keywords: Efforts, Independence